2016
DOI: 10.1155/2016/7478219
|View full text |Cite
|
Sign up to set email alerts
|

HDR Pathological Image Enhancement Based on Improved Bias Field Correction and Guided Image Filter

Abstract: Pathological image enhancement is a significant topic in the field of pathological image processing. This paper proposes a high dynamic range (HDR) pathological image enhancement method based on improved bias field correction and guided image filter (GIF). Firstly, a preprocessing including stain normalization and wavelet denoising is performed for Haematoxylin and Eosin (H and E) stained pathological image. Then, an improved bias field correction model is developed to enhance the influence of light for high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…T. harzianum Th33 in this study is a biocontrol fungi used in controlling plant fungal diseases caused by R. solani , Sclerotium rolfsii , Sclerotinia sclerotiorum , F. oxysporum , and Pythium spp. (Sun et al 2016 ). Deleting thga3 resulted in a significant decrease in antagonistic and mycoparasitic ability, which is similar to GzGPA2 in F. graminearum , wherein deletion of GzGPA2 caused reduced pathogenicity and increased chitin accumulation in the cell wall (Yu et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T. harzianum Th33 in this study is a biocontrol fungi used in controlling plant fungal diseases caused by R. solani , Sclerotium rolfsii , Sclerotinia sclerotiorum , F. oxysporum , and Pythium spp. (Sun et al 2016 ). Deleting thga3 resulted in a significant decrease in antagonistic and mycoparasitic ability, which is similar to GzGPA2 in F. graminearum , wherein deletion of GzGPA2 caused reduced pathogenicity and increased chitin accumulation in the cell wall (Yu et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Gα3 gene thga3 of T. harzianum Th33 was cloned from the Th33 genomic DNA (GenBank Accession Number PRJNA272949) (Sun et al 2016 ). The thga3 deletion strain Δ thga3 was generated by the double-crossover homologous recombination strategy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the multidimensional nature of health and aging 7 , recently more researches have paid attention to the relationship between diseases, such as chronic diseases, disability, and depression, and indicated that estimating one direction of the interrelationship between diseases may be misleading 8 10 . Several studies have explored disease, disability or depression trajectories among older adults, but they were estimated separately as if three independent processes 7 , 11 . To our knowledge, none of the studies examined the disability, depression and disease trajectories jointly and how the three components evolved over time.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is a very important task but, in any case, an experimental identification is time-consuming, highly-costly and laborious. To cope with this issue, a computational methodology is required for prediction of these proteins (Jiang et al 2016 ; Li et al 2016 ), however, no prior method exists.
Fig.
…”
Section: Introductionmentioning
confidence: 99%